(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article highlights the problem of the role of physical education in the formation of the health culture of students of higher education institutions. One of the promising directions for optimizing physical education with students of special medical groups is the rational use of special means and methods aimed at acquiring knowledge, skills and abilities to perform motor actions and develop motor qualities in order to strengthen their health, increase the level of physical development and physical fitness. The popularity among young people and the significant effectiveness of the impact on the body of the game of badminton determined the inclusion of this type of motor activity in the system of physical education of students of higher education institutions, and the possibility of variable load allows it to be used as a rehabilitation tool not only in groups of general physical training, but also in special medical groups . Thus, the results of scientific research and the conducted questionnaire allow us to believe that the educational and health potential of badminton classes is a significant factor in optimizing the system of physical culture and health work with students of higher education institutions. It is conditioned by: firstly, the fact that playing badminton contributes to the formation of positive motivation for systematic motor activity and sports, forms healthy lifestyle skills and an active lifestyle. The educational and physical and recreational potential of badminton is considered in the fact that the structure of its motor actions is based on natural human movements (running, jumping, leaning, changing the direction of movements, etc.), in the manifestation of psychophysical abilities, as well as expediency its use with insignificant financial costs in physical culture and health activities with student youth.